Social Classes Reflected By The Main Characters In Kevin Kwan’s “Crazy Rich Asians” Novel - Difa Reza Pahlevi; Eka Margianti Sagimin (IAIN Salatiga, 2020)
The aim of this study is to analyze the disparity of social class and the causes and effects of social class among two main characters in Kevin Kwan’s “Crazy Rich Asians” novel (2013). To analyze the issue, Weber’s theory of social class (1998) were used. The research methodology used in this study was a qualitative method. By using this method, it means a qualitative approach is used to describe the social phenomenon, life experiences and situations to give the meanings and also to explore the behavior, perspectives, experiences, and feeling of people in the form of an essay. Based on the analysis, some aspects that relate to the disparity and causes and effects of social class. Those are the types of social class disparity reflected by these two characters, the cause of social class between the two main characters and the effect that caused by its disparity of social class. The result of this study showed that these disparities can be lifestyle, ways of thinking and in choosing a partner. Also, social class can be caused by heredity and family background, the effects are someone who has a social class that is considered low, will be ostracized, or even terrorized.Keyword : Qualitative Method, Social Class, Weber Theory.